Ethanol Extract Guava Leaves (Psidium Guajava) Give Antidiabetic Effect On Male Mice With Alloxan Induction - Tiara Ajeng Listyani; Aisyah Rabitha Alisi; Tatiana Siska Wardani (LPPM Universitas Duta Bangsa Surakarta, 2022)
Diabetes mellitus is a chronic condition caused by increasing glucose level in blood. Long term use of antidiabetic drugs can cause various unwanted side effects, which makes people with diabetes try to use natural materials to control blood glucose levels. The aim of this study was to determine the antidiabetic activity of ethanol extract guava leaves (Psidium guajava) on male mice with alloxan induction. Mice were induced intravenously by alloxan dose of 160 mg/kg bw. After 7 days, mice were diabetic (blood glucose levels > 175 mg/dL) and were divided into 5 groups: negative control group (only treated with CMC-Na) ,positive control group (glibenclamide 0.65 mg/kg bw) and the 3 other groups were given ethanol extract guava leaves (Psidium guajava) at doses of 150 ,300 and 600 mg/kg bw. Dosage administered for 15 days and blood glucose levels was checked every 3 days using a glucotest. Data were analyzed by LSD (Least Significant Difference). Ethanol extract guava leaves (Psidium guajava) at doses of 150 ,300 and 600 mg/kg bw can lower blood sugar levels from day 3 to day 15 and was significantly different compared to the negative control group (p<0,05). Ethanol extract guava leaves (Psidium guajava) at doses of 150 ,300 and 600 mg/kg bw showed antidiabetic activity on male mice with alloxan induction.